2014
DOI: 10.3390/nu6041737
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Anti-Osteoporosis Properties of Diverse Korean Drynariae rhizoma Phenolic Extracts

Abstract: Drynariae rhizoma has been used to prevent bone loss that occurs with increasing age. However, the chemical compounds in extracts that act on bone metabolism in herbal medicine are poorly understood. This study aimed to investigate and compare the extraction efficacy of polyphenolic compounds, antioxidant activity, and in vitro anti-osteoporosis properties of water extract (DR-DW) and ethanol extract (DR-EtOH) from D. rhizoma. Total phenolics and flavonoids were better extracted with 70% EtOH, and this extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 45 publications
(61 reference statements)
2
10
0
Order By: Relevance
“…EDHB is a polyphenol found in many plants, e.g., peanut seed testa. EDHB has been the subject of interest of the scientists for its various properties, including antibacterial and antioxidant [20], cardioprotective [21], myoprotective [22] anti-osteoporosis activity [23], chelating iron bounding enzymes [24] and modifying hypoxia tolerance [25]. Moreover, there are reports indicating that collagen production can be reduced by EDHB, due to its abilities to inhibit prolyl hydroxylase [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…EDHB is a polyphenol found in many plants, e.g., peanut seed testa. EDHB has been the subject of interest of the scientists for its various properties, including antibacterial and antioxidant [20], cardioprotective [21], myoprotective [22] anti-osteoporosis activity [23], chelating iron bounding enzymes [24] and modifying hypoxia tolerance [25]. Moreover, there are reports indicating that collagen production can be reduced by EDHB, due to its abilities to inhibit prolyl hydroxylase [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Gu-Sui-Bu (GSB) has been used for the treatment of fractures, osteoporosis, rheumatoid arthritis, and head injuries (Shih et al, 2012; Wang et al, 2012; Saravanan et al, 2013; Liao et al, 2015). Studies have reported that extracts of Gu-Sui-Bu exhibit immune-promoting, anti-inflammatory, antiosteoporotic, and neuroprotective activities (Anuja et al, 2010; Chen et al, 2011b; Wang et al, 2012; Saravanan et al, 2013; Kang et al, 2014; Wang et al, 2016b). The natural compounds of Gu-Sui-Bu include naringin and flavonoids (Wang et al, 2008; Chen et al, 2011b).…”
Section: Resultsmentioning
confidence: 99%
“…More and more Chinese herbs have been historically used to treat bone metabolic diseases and known for anti-osteoporotic drugs [ 48 51 ]. The anti-osteoporosis effect of Rhizoma Drynariae and its extracts have attracted world-wide attention [ 52 , 53 ]. Our systematic review is to assess the efficacy and safety of Qianggu Capsule ( Rhizoma Drynariae ) in osteoporosis therapy.…”
Section: Discussionmentioning
confidence: 99%